2019
DOI: 10.1177/0361198119847616
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Placement of Reservation-Based Intersections in Urban Networks

Abstract: Reservation-based traffic control is a revolutionary intersection management system which involves the communication of autonomous vehicles and an intersection to request space-time trajectories through the intersection. Although previous studies have found congestion and throughput benefits of reservation-based control that surpass signalized control, other studies have found negative impacts at peak travel times. The main purpose of this paper is to find and characterize favorable mixed configurations of res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
0
0
0
Order By: Relevance
“…This strategy has been validated using real data from the Beijing Metro's Batong Line, yielding a high-quality carriage reservation plan within a short computational timeframe. Furthermore, when the reservation proportion falls within an appropriate range, it reduces travel time [35]. When Mei et al studied reserved parking spaces, they found that when the proportion of reserved vehicles is not high, congestion in popular parking lots may intensify [36].…”
Section: Introductionmentioning
confidence: 99%
“…This strategy has been validated using real data from the Beijing Metro's Batong Line, yielding a high-quality carriage reservation plan within a short computational timeframe. Furthermore, when the reservation proportion falls within an appropriate range, it reduces travel time [35]. When Mei et al studied reserved parking spaces, they found that when the proportion of reserved vehicles is not high, congestion in popular parking lots may intensify [36].…”
Section: Introductionmentioning
confidence: 99%